Investigation of the Properties of Hydrogels Based on Acrylic Acid and Diamines - A.E. Kurbanbaeva; D.A. Holmuminova (Genius Journals, 2023)
The electrochemical properties and swelling abilities of new hydrogels of acrylic acid derivatives in an aqueous solution, as well as their conformational transformations during the transition from one state to another, have been studied. The mutual influence of the physicochemical parameters of aqueous solutions, including electrical conductivity, pH media, and the swelling coefficient of hydrogels, has been studied. It has been established that during the ionization of hydrogels in an aqueous medium, intramolecular associates are formed with the participation of a proton and carboxylate anions, stabilized by hydrophobic interactions of the network structure of a sparsely crosslinked polyelectrolyte. It is shown that this process is accompanied by a sharp change in the pH values of the medium, an increase in the electrical conductivity and the swelling coefficient of the hydrogel in water.
Keywords: hydrogel; electrical conductivity; aqueous solution